Peptidoglycan from fermentation by-product triggers defense responses in grapevine. - Yang Chen; Taito Takeda; Yoshinao Aoki; Keiko Fujita; Shunji Suzuki; Daisuke Igarashi (PLoS ONE)
Plants are constantly under attack from a variety of microorganisms, and rely on a series of complex detection and response systems to protect themselves from infection. Here, we found that a by-product of glutamate fermentation triggered defense responses in grapevine, increasing the expression of defense response genes in cultured cells, foliar chitinase activity, and resistance to infection by downy mildew in leaf explants. To identify the molecule that triggered this innate immunity, we fractionated and purified candidates extracted from Corynebacterium glutamicum, a bacterium used in the production of amino acids by fermentation. Using hydrolysis by lysozyme, a silkworm larva plasma detection system, and gel filtration analysis, we identified peptidoglycan as inducing the defense responses. Peptidoglycans of Escherichia coli, Bacillus subtilis, and Staphylococcus aureus also generated similar defensive responses.